The Analysis Study of Prevalence, Diagnosis and Management of Chronic Obstructive Pulmonary Disease (COPD): A Comprehensive Systematic Review - Mushlihin, Amrul; Ramadhan, Fitratul (International Medical Journal Corp. Ltd, 2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a debilitating respiratory condition that significantly contributes to global morbidity and mortality rates. This systematic review aims to evaluate prevalence, diagnostic challenges, and management strategies for COPD based on the literatures of the last 10 years. Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: COPD is a major global health issue, significantly impacting quality of life due to prevalent comorbidities. This review emphasizes the necessity for targeted interventions and innovative management strategies, including home-based treatments, to enhance patient outcomes and reduce healthcare costs.